Analisis Kompetensi Strategis Matematis Siswa SMA dalam Menyelesaikan Masalah Statistika Bivariat - Avita Nurannisa Rahayu; Nita Hidayati; Agung Prasetyo Abadi (Program Studi Pendidikan Matematika, FSTT, Universitas Pendidikan Mandalika, 2026)
The purpose of this study is to analyze the mathematical strategic competence of high school students in solving bivariate statistics problems in terms of their strategic competence categories. The method used was descriptive with a quantitative approach. The research sample consisted of 33 eleventh-grade students at MAN Purwakarta in the second semester of the 2025/2026 academic year, selected through purposive sampling. The research instrument consisted of four essay questions developed based on strategic competence indicators, namely formulating, representing, and solving problems. The data were analyzed using descriptive statistics through calculations of the mean, standard deviation, maximum value, minimum value, and the percentage of achievement for each indicator. The analysis showed that the average strategic competence score of the students was 67.03 with a standard deviation of 14.63. Most students (69.70%) were in the moderate category, while 15.15% were in the high category and 15.15% were in the low category. The representation indicator obtained the highest achievement percentage at 81.4%, followed by the formulation indicator at 74.5%, and the problem-solving indicator at 54.3%. Overall, these findings indicate that students' strategic competence in bivariate statistics still needs further improvement, particularly in the problem-solving aspect. These results imply the need for instruction that emphasizes systematic, data-based problem-solving practice in bivariate statistics